Vertically oriented epitaxial germanium nanowires on silicon substrates using thin germanium buffer layers - Jung, J; Yoon, H; Kim, Y; Song, MS; Kim, Y; Chen, Z; Zou, J; Choi, D; Kang, J; Joyce, H; Gao, Q; Hoe Tan, H; et al. (2010)
We demonstrate a method to realize vertically oriented Ge nanowires on Si(111) substrates. Ge nanowires were grown by chemical vapor deposition using Au nanoparticles to seed nanowire growth via a vapor-liquid-solid growth mechanism. Rapid oxidation of Si during Au nanoparticle application inhibits the growth of vertically oriented Ge nanowires directly on Si. The present method employs thin Ge buffer layers grown at low temperature less than 600 °C to circumvent the oxidation problem. By using a thin Ge buffer layer with root-mean-square roughness of ∼ 2nm, the yield of vertically oriented Ge nanowires is as high as 96.3%. This yield is comparable to that of homoepitaxial Ge nanowires. Furthermore, branched Ge nanowires could be successfully grown on these vertically oriented Ge nanowires by a secondary seeding technique. Since the buffer layers are grown under moderate conditions without any high temperature processing steps, this method has a wide process window highly suitable for Si-based microelectronics. © 2010 IOP Publishing Ltd.